2020
DOI: 10.14295/ambeduc.v25i2.11521
|View full text |Cite
|
Sign up to set email alerts
|

Educação ambiental, educação do campo e ambientalização escolar: diálogos entre diversas paisagens escolares

Abstract: A educação ambiental tem sido uma oportunidade de aproximar os diversos campos dos conhecimentos, saberes e vivências como a ambientalização escolar e a educação do campo. A ambientalização escolar é aqui discutida como um possível caminho metodológico para trabalhar a dimensão socioambiental na gestão, currículo e espaço nos processos educadores que objetivam constituir territórios sustentáveis para a percepção, valoração e transformação das paisagens escolares. Assim, para que possam ser fortalecidas escolas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is observed that the State is incapable of attending to the great diversity and heterogeneity of rural people in the Amazon. This worrying consideration anchors the perspective that the offer of basic rights to the field follows the perspective of offering, as Sammarco et al [34] emphasize, "a poor education to the rural poor".…”
Section: Field Education and Appreciation Of The Rural Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the State is incapable of attending to the great diversity and heterogeneity of rural people in the Amazon. This worrying consideration anchors the perspective that the offer of basic rights to the field follows the perspective of offering, as Sammarco et al [34] emphasize, "a poor education to the rural poor".…”
Section: Field Education and Appreciation Of The Rural Environmentmentioning
confidence: 99%
“…When analyzing the inserting of EE in higher education, socio-environmental issues inherent to EE is still little contemplated [34] . Silva and Chelotti [40] affirm that the training of teachers does not give provide subsidies to foster EE, which causes gaps in teacher training.…”
Section: Environmental Education As a Transversal Themementioning
confidence: 99%
“…Apesar das importâncias que ambas possuem para o ensino-aprendizagem dos estudantes, diversos estudos revelaram que a EA não vem sendo utilizadas de forma efetivas pelos docentes das escolas do/no campo (Zuchini et al, 2013;Sanches & Moreira, 2019;Miranda 2017;Silva et al, 2019;Sammarco et al, 2020). Principalmente, nas escolas localizadas na Amazônia, onde os problemas ambientais influenciam diretamente na conservação e usos sustentáveis dos ecossistemas (Oliveira et al, 2019;Cardoso et al, 2021).…”
Section: Introductionunclassified